Popular economics what the Rolling Stones, Downton Abbey, and LeBron James can teach you about economics - Tamny, John (Washington, DC Regnery Publishing, 2015)
"John Tamny uses entertaining stories from sports, movies, popular culture, and famous businesses to explain the basic principles of economics. His Dollars and Sense is an everyman's guide to how money really works-a lesson politicians try (and fail) to grasp every day. "--Provided by publisher.
Keywords: Economics; Electronic books